Lightish but clumpy: scalar dark matter from inflationary fluctuations - Alonso Álvarez, Gonzalo; Jaeckel, Joerg (Journal of cosmology and astroparticle physics, 2018)
It has recently been shown [1] that light vector particles produced from inflationary fluctuations can give rise to the dark matter in the Universe. A similar mechanism has been discussed in [2] for a non-minimally coupled scalar enjoying a Higgs portal interaction. We discuss in detail how such a generation of dark matter works in a minimal setup of a massive scalar non-minimally coupled to gravity. For suitable values of the non-minimal coupling any initial constant value of the field is suppressed during inflation. At the same time, the quantum fluctuations acquired during inflation give rise to a peaked energy density power spectrum. Isocurvature constraints can be avoided since nearly all of the energy is concentrated in fluctuations too small to be observed in the CMB. For masses ##IMG## [http://ej.iop.org/icons/Entities/gtrsim.gif] gtrsim eV and sufficiently high inflation scale the energy contained in these fluctuations is sufficient to account for the cold dark matter of the Universe. At small scales ℓ today 10 4 km √(m/eV) 10 -4 AU √(m/eV) fluctuations are large and we therefore expect a rather clumpy nature of this form of dark matter.